The Exsistence of Rain in the Tafsir Fii Zhilalil Qur'an by Sayyid Qutb - Syarif, Muhammad Abdullah (Getpress Management Journals, 2024)
This study aims to reveal the symbolic meaning of rain in Tafsir Fii Zhilalil Qur'an by Sayyid Qutb, with a qualitative approach through content analysis method. The results of the study show that Sayyid Qutb interprets rain in the Qur'an as a symbol that represents several important aspects of Islamic teachings. (1) rain is understood as a symbol of Allah's mercy, which shows His compassion and grace to all living things. (2) rain is also a symbol of Allah's power, reminding humans of His greatness in regulating the universe. (3) rain is seen as a symbol of Allah's warning, which reminds humans of the cycle of life and the importance of selfintrospection. (4) rain becomes a symbol of Allah's resurrection, because the rainwater that falls becomes a source of life for nature and living things. This article emphasizes that Sayyid Qutb gives deep meaning to rain as a symbol of "reminder" as well as for all of nature.. Thus, this study emphasizes the importance of semantic analysis in understanding the profound messages contained in the Qur'an.